Factors Affecting Students’ Presence (Case Study: Private Kindergarten, Gonbad-E-Qabus, Iran) - Haghighat, Tina (2012)

(untitled)
This research investigates the underlying factors affecting students‟ presence based on learning environment facilities. The places that are relevant with children learning should include appropriate environment to improve their physical, mental and social growth. This is possible by utilizing suitable architectural elements and by designing a place that children use to learn. Architectural forms originate from special and specific elements. Kindergarten is the first educational and social place that children experience. It is also one of the important learning spaces in early childhood that has effects on children‟s education. In this environment children go through basic learning experience.